2009
DOI: 10.1111/j.1467-9604.2009.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring support for dyslexic adults in the English workforce: lessons learnt from the story of an adult dyslexia group

Abstract: Dyslexia support is likely to be in place for students within educational establishments in England. However, there are a significant number of adults with dyslexia in the English workplace who are no longer involved in education and for whom ongoing support is necessary to enable them to reach their potential in a world of increasing literacy demands. Legislation has led to significant moves towards inclusion in the English workplace, but there has been a lack of public recognition of the concerns and needs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Qualitative research has demonstrated that individuals with dyslexia utilise numerous coping strategies in managing the challenges and difficulties they face as a result of their dyslexia [51,52]. Correspondingly, it would be a worthwhile pursuit to support individuals with dyslexia to change their attribution style from pessimistic to optimistic [53].…”
Section: Coping With Dyslexiamentioning
confidence: 99%
“…Qualitative research has demonstrated that individuals with dyslexia utilise numerous coping strategies in managing the challenges and difficulties they face as a result of their dyslexia [51,52]. Correspondingly, it would be a worthwhile pursuit to support individuals with dyslexia to change their attribution style from pessimistic to optimistic [53].…”
Section: Coping With Dyslexiamentioning
confidence: 99%
“…However, less attention has been focused on the process of dyslexic adults entering the workforce [ 21 ]. Additionally, while legislative policies in Australia and overseas have been developed to protect people with dyslexia from discrimination [ 22 , 23 , 24 , 25 , 26 ], a commitment to those with dyslexia in workplaces has not been as well established [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors [ 1 , 24 , 31 , 32 ] reinforce the importance of training to be offered to employers and their leadership teams to improve their knowledge of dyslexia. It appears from the research that without a coordinated effort from employers, managers, workplace leaders and human resources staff to provide accommodations and adjustments, employees with dyslexia are likely to struggle to complete designated work tasks [ 24 , 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, instructors, learning strategists, and others working with adolescents and university students with RD should consider how to complement the development of learning strategies and skills with coaching on ways to seek out resources and encourage the development of a range of social ties on and off campus. Furthermore, little workplace support is available for adults with RD (Bell, 2009). Building a foundation of supports during postsecondary education may help transfer supports to activities after graduation.…”
Section: Discussionmentioning
confidence: 99%